1985
DOI: 10.1111/j.1365-3083.1985.tb01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Differentiation of Cord Blood Lymphocytes Induced by Thymosin Fraction 5 and Thymosin Alpha1

Abstract: Cord blood lymphocytes (CBL) have been shown to be functionally immature compared with normal circulating adult lymphocytes (NAL). Differentiation of T cells is associated with changes in surface antigenic markers and in the pattern of purine degradative enzymes. Previous studies have demonstrated that thymosin fraction 5 (TMS-F5) and thymosin alpha 1 (TMS-alpha 1) can induce in vitro differentiation of murine T-cell precursors and human thymocytes. We have investigated the effects of TMS-F5 and TMS-alpha 1 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
2
Order By: Relevance
“…In three reports, significant numbers (10-8, 14-2, and 24% of leucocytes) of CD-I + cells were found (7)(8)(9), and the authors cited these findings as indicating the presence of immature T cells in the neonatal circulation. Four other studies, however, documented lower (0-7-2-0%) numbers of these cells (2,6,20,22), a range more consistent with the present observations. The reasons for these discrepancies are presumably methodological.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In three reports, significant numbers (10-8, 14-2, and 24% of leucocytes) of CD-I + cells were found (7)(8)(9), and the authors cited these findings as indicating the presence of immature T cells in the neonatal circulation. Four other studies, however, documented lower (0-7-2-0%) numbers of these cells (2,6,20,22), a range more consistent with the present observations. The reasons for these discrepancies are presumably methodological.…”
Section: Discussionsupporting
confidence: 93%
“…metabolites (2), expression of peanut agglutinin receptor (3), reduced formation of rosettes with sheep erythrocytes (4,5), and expression of the stem-cell related antigen detected by monoclonal antibody (Moab) . Significant numbers of cord lymphocytes expressing the immature thymocyte antigen CD-1 detected by Moabs OKT-6 and NAl-34 have also been reported by several groups (7-9).…”
Section: Introductionmentioning
confidence: 99%
“…Sosne et al [30] reported that Th 4 acts as an anti-apoptotic agent in ethanol-treated human corneal epithelial cells. Notwithstanding these recent findings, however, the capacity of other thymic peptides to oppose cell death may be related to acute induction of differentiation, given that the thymosins promote cellular maturation in normal human lymphocytes [31][32][33][34][35] and stem cells [36]. While the mechanisms underlying anti-apoptotic actions of certain thymosins have not been completely delineated, cytoprotective systems associated with thymosin action include cPKC/nPKC and PKA [25,37] as well as by p125-FAK [28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Tα1 has been shown capable of increasing lymphocytic infiltration to sites of disease [ 63 , 64 , 65 , 66 , 67 ] while a correlation between tumor-infiltrating lymphocytes and prognosis for patients with stage IV cancer has been documented [ 68 ]. Moreover, Tα1 can reduce apoptosis of immune cells, as shown in mouse [ 69 , 70 ] and human [ 71 , 72 ] thymocytes, and increase stem cell expansion in immunosuppressed mice [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%